Analysis of the Implementation of PSAK 72, Return on Assets, Current Ratio and Company Size on Property Company Value - Regina, Rena; Kusuma, Indra Cahya; Didi, Didi (Institut Bisnis dan Informatika Kesatuan, 2024)
Measuring company value can be done by observing the development of share prices on the stock exchange. The continuing increase in share prices reflects that many investors believe in companies paying more so that investors will get high returns. The purpose of this research is to determine the effect of PSAK 72, return on assets, current ratio and company size which is proxied by the natural logarithm of assets on company value which is proxied by the Tobin's Q ratio. The population in this study is property, real estate and building construction companies which listed on the IDX in 2013-2022. The sampling technique in this research was purposive sampling with several specified criteria and resulted in 7 property, real estate and building construction companies. The data analysis method used is multiple linear regression with Eviews 12 software. The results of this research show that PSAK 72 partially has no effect on company value, ROA partially has a positive effect on company value, CR and company size partially have a negative effect on company value. PSAK 72, ROA, CR, and company size simultaneously influence company value.